2012
DOI: 10.1097/ico.0b013e3182254170
|View full text |Cite
|
Sign up to set email alerts
|

Pinguecula and Diabetes Mellitus

Abstract: This is the first assessment of the relationship between pinguecula and diabetes mellitus. Our results suggest that diabetes mellitus may be a factor associated with the development of pinguecula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…It follows that pinguecula protrusion may affect tear film stability and therefore TBUT, but we also found that tear film production improved postoperatively. This finding is supported by evidence in the literature of lower tear osmolarity after pterygium excision surgery [14]. Pinguecula and pterygium may influence aqueous tear production via friction against the tarsus causing local inflammation and decreasing accessory lacrimal gland secretion.…”
Section: Discussionsupporting
confidence: 71%
“…It follows that pinguecula protrusion may affect tear film stability and therefore TBUT, but we also found that tear film production improved postoperatively. This finding is supported by evidence in the literature of lower tear osmolarity after pterygium excision surgery [14]. Pinguecula and pterygium may influence aqueous tear production via friction against the tarsus causing local inflammation and decreasing accessory lacrimal gland secretion.…”
Section: Discussionsupporting
confidence: 71%
“…None of the population-based studies on the prevalence of pinguecula that included DM in the assessment found a relationship between the two [ 3 , 4 , 15 ]. However, results from the hospital-based study by Mimura et al [ 13 ] suggested that DM may be associated with the development of pinguecula, possibly due to deposition of AGEs, diabetic microvascular damage of conjunctival blood vessels, and diabetes-related eye dryness. We could not find a significant association between diabetes and the presence of pinguecula, nor between the severity of pinguecula and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Pinguecula was diagnosed when present in either eye. The severity of pinguecula was graded according to a scheme based on slit lamp examination findings ( Table 1 ) [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pterygium is a multifactorial condition that is mainly associated with aging and exposure to UVR. Because diabetes accelerates the aging process, it may contribute to the development of diseases typical of aging and that ocular aging may lead to the progression of pterygium (13).…”
Section: Discussionmentioning
confidence: 99%